Implementation of Fiqh al-I‘lām Principles for Library Information Services in the Digital Age - Abdurrasyiid Ridla; Anis Masruri (Daluang: Journal of Library and Information Science, 2026)
Purpose. Describe the structure of the rules of Fikih Informasi (Fiqh al-I‘lām), analyze the relevance of these values ​ and formulate a model for implementing the rules of Fikih Informasi (Fiqh al-I‘lām) in the context of library information services in the digital era. Methodology. This research use a library research method with a qualitative approach. Data sources in the form of books and article used as the object of the study. Results and discussion. Western information ethics and Fikih Informasi (Fiqh al-I‘lām) are grounded in fundamentally different normative paradigms. The normative foundation of Western information ethics is secular-humanistic, while that of Fikih Informasi (Fiqh al-I‘lām) is a religious-moral framework built upon the principles of Tawḥīd, Akhlāq Karīmah, and Maṣlaḥah. The findings indicate that applying Fikih Informasi (Fiqh al-I‘lām) functions as a vital framework for librarians to address and reduce information disasters such as disinformation, misinformation, malinformation, and hoaxes. Conclusions. This study concludes that Fikih Informasi (Fiqh al-I‘lām) provides a compatible ethical framework for libraries in religious and collectivist societies like Indonesia. It transforms the library from a mere information provider into a "center of wisdom". However, the current conceptualization of Fiqh al-I'lām remains confined to a linear, ethical-theocentric framework and lacks contextual adaptation to specific library types as well as concrete Standard Operating Procedures (SOP). Consequently, it is proposed that future research incorporate a socio-anthropocentric lens and adopt interdisciplinary methodologies to enhance the contextual adaptation of Fiqh al-I'lām for various library sectors and its translation into operational frameworks